2024
DOI: 10.1021/acsanm.3c05810
|View full text |Cite
|
Sign up to set email alerts
|

α-MoO3 Microflakes Decorated with Gold Nanoislands as SERS-Active Substrates

Vimarsh Awasthi,
Sharmistha Dey,
Pankaj Srivastava
et al.

Abstract: Surface-enhanced Raman spectroscopy (SERS) is an effective method that can be employed to detect analytes in ultratrace amounts precisely. The extensive development of noble-metal-based SERS detection has been done in the recent past. A hybrid of noble metals and semiconductors is highly effective in enhancing the Raman signal in addition to making it a stable, large-area, and low-cost SERS substrate, enabling the rapid growth of these heterostructures in SERS-based research areas. Defect engineering is a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…α-MoO 3 , as a natural van der Waals crystal, exhibits a range of electronic states from semiconductor to metallic through intentional doping with defects and impurities. Above all, metallic behaviors of α-MoO 3 can generate localized SPRs (LSPRs), contributing to the enhancement of Raman signals through an EM process. , The previous studies have reported SERS applications based on hybrid structures of α-MoO 3 and metallic nanostructures . Strongly localized electromagnetic fields on metallic nanostructures are useful for the improvement of the SERS responses.…”
Section: Introductionmentioning
confidence: 99%
“…α-MoO 3 , as a natural van der Waals crystal, exhibits a range of electronic states from semiconductor to metallic through intentional doping with defects and impurities. Above all, metallic behaviors of α-MoO 3 can generate localized SPRs (LSPRs), contributing to the enhancement of Raman signals through an EM process. , The previous studies have reported SERS applications based on hybrid structures of α-MoO 3 and metallic nanostructures . Strongly localized electromagnetic fields on metallic nanostructures are useful for the improvement of the SERS responses.…”
Section: Introductionmentioning
confidence: 99%